PERSIAPAN MASA PURNABAKTI, PENTINGNYA PENINGKATAN PENGETAHUAN POLA HIDUP SEHAT DAN MENGATASI MASALAH KESEHATAN PADA USIA PENSIUN - Mustofa, Syazili; Sani, Nanda Apri (CV. Jasa Sukses Abadi, 2024)
Retirement is a crucial phase and must be well-prepared. Retirement is the end of regular work and entering a period of rest. Someone approaching retirement age should be prepared with knowledge about healthy lifestyle and various health issues and their management. This will increase individual preventive efforts to maintain their health. Healthy lifestyle can be achieved by consuming a balanced nutritious diet, engaging in proper and regular physical activities or exercises, managing stress well, avoiding smoking, and maintaining personal hygiene. In addition, health problems can occur in the elderly because as they age, the physiological abilities of the body decline, increasing the risk of degenerative diseases such as hypertension, musculoskeletal problems, diabetes, heart attacks, strokes, chronic kidney disease, and cancer. These diseases can be managed by recognizing symptoms, seeking early treatment, and preventing them before they occur. Knowledge about retirement preparation about healthy lifestyle and various health issues and their management is essential to improve the quality of life during retirement.